The relationship among cognitive flexibility, self-criticism and depression considering the moderating role of emotion regulation in female students with depression symptoms - Mirshafiei , Negar Sadat; Mohammadi, Maryam (Social Determinants of Health, 2024)
Background: The goal of this study was to examine how self-criticism and cognitive flexibility relate to depression, taking into account the moderating effect of emotion control in depressed undergraduate females. Methods: The present study's statistical population consisted of all female students at Isfahan Azad University in 1402 who exhibited signs of depression. 384 people were chosen using cluster random selection from the study's target population as a sample, using Cochran's formula. The research variables were measured using the Beck Depression Inventory, the Gross & John Emotion Regulation Questionnaire, the Gilbert et al. Self-Criticism Scale, the Dennis & Vander Wal Cognitive Flexibility Inventory, and the questionnaire on demographic characteristics. The acquired data were examined using the regression analysis technique and the statistical program SPSS version 27. Results: Findings showed that there is a significant relationship between cognitive flexibility and self-criticism with depression, cognitive flexibility and self-criticism with emotion regulation, and also between emotion regulation and depression (p<0.01). Also, the findings indicated that emotion regulation has a moderating role in the relationship between cognitive flexibility and self-criticism with depression (p<0.01). Conclusion: Based on the findings of this research, it can be concluded that the relationship between cognitive flexibility and self-criticism with depression is not a simple linear relationship and emotion regulation can affect this relationship.